Gestión del costo en el diseño y confección de prendas de vestir a través del sistema por órdenes de producción (2024)
The following research aimed to manage the cost of production in the design and manufacture of garments, identifying the different processes and activities that consume resources, applying accumulation systems that allow you to know the elements of the cost that are involved, which will later make it easier to determine the cost of production, its contribution margin and make different business decisions to the entrepreneur responsible for the business.